Reactivity of Glycolaldehyde towards Hexacyanoferrate(III) in Alkaline Medium and Mechanism of the Reaction - Kali Sen Gupta, Kalayan; A.B., Bilkis; Kumar Bera, Ashok (Asian Journal of Chemistry, 2010)
The oxidative behaviour of glycolaldehyde towards hexacynoferrate(III) in alkaline medium has been investigated. The reaction obeys the following rate expression: where k3 = 100.0 ± 2 mol–2 dm6s–1 at 298 K. The values of ΔH≠ and ΔS≠ are 51 ± 4 kJ mol–1 and –35 ± 13 JK–1 mol–1 respectively. The reactions appear to proceed through the intermediate formation of alkoxide ion to glyoxal.